Assessing "Spin" in Urology Randomized Controlled Trials With Statistically Nonsignificant Primary Outcomes. Issue 3 (23rd March 2023) - Wu, Jeremy; Ho, Wilson; Klotz, Laurence; Yuan, Morgan; Lee, Jason Y.; Krakowsky, Yonah
Abstract : Purpose: "Spin" refers to a form of language manipulation that positively reflects negative findings or downplays potential harms. Spin has been reported in randomized controlled trials of other surgical specialties, which can lead to the recommendation of subpar or ineffective treatments. The goal of this study was to characterize spin strategies and severity in statistically nonsignificant urology randomized controlled trials. Materials and Methods: A comprehensive search of MEDLINE and Embase for the top 5 urology journals, major urology subspecialty journals, and high-impact nonurology journals from 2019 to 2021 was conducted. Statistically nonsignificant randomized controlled trials with a defined primary outcome were included. Screening, data extraction, and spin assessment were performed in duplicate by 2 independent reviewers. Results: From the database search of 4, 339 studies, 46 trials were included for analysis. Spin was identified in 35 studies (76%), with the majority of abstracts (n = 26, 57%) and main texts (n = 35, 76%) containing some level of spin. "Obscuring the statistical nonsignificance of the primary outcome and focusing on statistically significant secondary results" was the most frequently used strategy in abstracts, while "other" strategies not previously defined were the most commonly used strategies in main texts. Moderate or high spin severity was identified in 21 (46%) abstract and 22 (48%) main text conclusions. Conclusions: Overall, our results suggest that 76% of statistically nonsignificant urology randomized controlled trials contained some level of spin. Readers and writers should be aware of common spin strategies when interpreting nonsignificant results and critically appraise the significance of results when making decisions for clinical practice.